Open conformation of tetraspanins shapes interaction partner networks on cell membranes. (16th August 2020) - Yang, Yihu; Liu, Xiaoran Roger; Greenberg, Zev J; Zhou, Fengbo; He, Peng; Fan, Lingling; Liu, Shixuan; Shen, Guomin; Egawa, Takeshi; Gross, Michael L; Schuettpelz, Laura G; Li, Weikai
Abstract: Tetraspanins, including CD53 and CD81, regulate a multitude of cellular processes through organizing an interaction network on cell membranes. Here, we report the crystal structure of CD53 in an open conformation poised for partner interaction. The large extracellular domain (EC2) of CD53 protrudes away from the membrane surface and exposes a variable region, which is identified by hydrogen–deuterium exchange as the common interface for CD53 and CD81 to bind partners. The EC2 orientation in CD53 is supported by an extracellular loop (EC1). At the closed conformation of CD81, however, EC2 disengages from EC1 and rotates toward the membrane, thereby preventing partner interaction. Structural simulation shows that EC1‐EC2 interaction also supports the open conformation of CD81. Disrupting this interaction in CD81 impairs the accurate glycosylation of its CD19 partner, the target for leukemia immunotherapies. Moreover, EC1 mutations in CD53 prevent the chemotaxis of pre‐B cells toward a chemokine that supports B‐cell trafficking and homing within the bone marrow, a major CD53 function identified here. Overall, an open conformation is required for tetraspanin–partner interactions to support myriad cellular processes. Synopsis: Crystal structure of CD53 captures an open conformation for partner interaction and reveals the structural regulation mechanism for tetraspanins to organize interaction networks on cell membranes and support myriad cellular processes. Crystal structure of CD53 captures an open conformation poised for partner interaction. This open conformation is supported by a stable EC1‐EC2 interaction. Hydrogen‐deuterium exchange experiments show that CD53 and CD81 use their C‐D variable region in the EC2 domain to bind partners. This variable region approaches the membrane plane in the closed conformation, and through EC2 rotation in the open conformation, the above‐membrane height of this region is raised to permit partner interaction. Partner specificity of tetraspanins is achieved by the various structures and sequences of the C‐D region, by its above‐membrane height that matches with interacting partners, and by interactions through the transmembrane domains. CD53 assists the migration of pre‐B cells towards the CXCL12 chemokine, whereas disrupting the EC1‐EC2 interaction abolishes this migration. Similar EC1 mutations in CD81 impairs the accurate glycosylation of CD19. Abstract : The first structures of the open conformation of a tetraspanin membrane receptor reveals how rotation of the CD53 extracellular domain affects binding interactions that promote downstream cellular processes such as migration.